Gambaran Kualitas Tidur, Kecemasan dan Kelelahan Pasien Kanker Dengan Pengobatan Kemoterapi di RSUP Dr M Djamil Padang - Maharani, Andika; Neherta, Meri; Lidya, Lidya (Universitas Fort De Kock Bukittinggi, 2024)
Background: Sleep disturbances, anxiety and fatigue are potential problems that can occur in chemotherapy patients. The aim of this research is to describe sleep quality, anxiety and fatigue in chemotherapy patients. Methods: Descriptive research with a sample of 47 chemotherapy patients selected by purposive sampling technique. Data were collected using a questionnaire. Results: The results showed that all respondents had poor sleep quality (100%), the majority respondents (61.7%) had moderate anxiety levels and the majority respondents (76.6%) experienced moderate fatigue levels. Conclusion: The results of this study illustrate that chemotherapy treatment in cancer patients contributes to poor sleep quality, anxiety and fatigue. So that the role of nurses is needed to improve sleep quality, reduce anxiety and fatigue in chemotherapy patients.Keywords: chemotherapy; cancer; sleep quality; anxiety; fatigue